2021
DOI: 10.1016/j.onehlt.2021.100244
|View full text |Cite
|
Sign up to set email alerts
|

Data quality and arbovirus infection associated factors in pregnant and non-pregnant women of childbearing age in Brazil: A surveillance database analysis

Abstract: The dengue surveillance system in Brazil has registered changes in the disease's morbidity and mortality profile over successive epidemics. Vulnerable groups, such as pregnant women, have been particularly hard hit. This study assessed the quality of notifications of dengue cases among pregnant women and non-pregnant women of childbearing age in Brazil, in addition to discussing the factors associated with arbovirus infection in the group of pregnant women. We carried out a retrospective study of cases registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Particularly in Brazil, in a retrospective study carried out with data from 2007 to 2017, Einlof et al [ 45 ] described that the age group of 20–29 years was the most frequent in women diagnosed with dengue, especially in pregnant women. Taken together, these data suggest higher vulnerability in this age group, probably related to behavioral and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in Brazil, in a retrospective study carried out with data from 2007 to 2017, Einlof et al [ 45 ] described that the age group of 20–29 years was the most frequent in women diagnosed with dengue, especially in pregnant women. Taken together, these data suggest higher vulnerability in this age group, probably related to behavioral and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important issue and deserves further investigation, especially when considering the risk of congenital Zika syndrome and the fact that the age group of 20–39 years (childbearing age) is among the most diagnosed in our study. Despite this, some authors reported difficulties in carrying out a more in-depth analysis in this population due to the lack of data on pregnancy during the notification of arboviruses [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…O objetivo do SINAN é coletar, transmitir e disseminar os dados gerados rotineiramente pela vigilância epidemiológica das três esferas de governo, por intermédio de uma rede informatizada, para apoiar o processo de investigação e dar subsídios à análise das informações das doenças de notificação compulsória (Brasil, 2006). No entanto, estudos apontam que o mesmo é subutilizado, impactando, por conseguinte sua função de gerar informações para o planejamento em saúde (Moraes & Duarte, 2009;Rocha et al, 2020;Einloft et al, 2021).…”
unclassified